2011
DOI: 10.1017/s1047951111000771
|View full text |Cite
|
Sign up to set email alerts
|

Accidental intra-arterial injection of adenosine in a patient with supraventricular tachycardia

Abstract: Supraventricular tachycardia is the most common symptomatic arrhythmia in children. Acute management in haemodynamically stable patients is pharmacological. The drug of choice is adenosine, a metabolite of adenosine triphosphate, which causes conversion to sinus rhythm by transient atrioventricular block. 1 We describe the case of a 12-year-old girl with supraventricular tachycardia due to Wolff-ParkinsonWhite syndrome. The tachycardia started during physical exercise and both Valsalva manoeuvre and administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…24 The side effects of medication like adenosine, neostigmine---atropine combination and neostigmine---glycopyrrolate have not been reported. 38,39 It is known that more complications are caused by membranesoluble medications. 4 Babacan et al 30 in a study researching the histopathological criteria of intra-arterial effects of thiopental and propofol in rabbits found that intra-arterial administration of 2.5% thiopental may be responsible for gangrenous changes and though this effect was not found with 1% propofol, they concluded it could cause clear edema.…”
Section: Discussionmentioning
confidence: 99%
“…24 The side effects of medication like adenosine, neostigmine---atropine combination and neostigmine---glycopyrrolate have not been reported. 38,39 It is known that more complications are caused by membranesoluble medications. 4 Babacan et al 30 in a study researching the histopathological criteria of intra-arterial effects of thiopental and propofol in rabbits found that intra-arterial administration of 2.5% thiopental may be responsible for gangrenous changes and though this effect was not found with 1% propofol, they concluded it could cause clear edema.…”
Section: Discussionmentioning
confidence: 99%